Ceo Tenure As a Determinant of Ceo Pay - Hill, Charles W. L.; Phan, Phillip (Academy of Management Journal, 1991)
Our hypotheses were that the influence of chief executive officers (CEOs) over boards of directors and the likelihood that the CEOs' compensation packages will reflect their preferences increase with CEO company tenure. Results of empirical tests were consistent with this argument, suggesting that the relationship between CEO pay and stock returns weakens with tenure.